SYNTHESIS AND CHARACTERIZATION OF A COMPLEX OLIGOMERIC 1,1 '-BIS (OCTADECYL) -2,2'-BIBENZIMIDAZOLE AND COBALT (II) - Ninan M., Óscar (2007)
The preparation of an oligomeric complex obtained from the reaction of 1,1'-bis(octadecyl)-2,2'-benzimidazole and CoCl2 is reportad. This oligómero has been characterized by UV-visible spectroscopy, FT-IR and 1 H-RMN. The elemental analysis does not throw a defined relation between cobalt and the ligand. The oligomeric complex undergoes decomposition when heating according to ose analysis.